The Correlation between Students’ Writing Anxiety and Writing Achievement of Students’ English Department at Universitas Negeri Padang - Ayu Andira; Edi Trisno (Journal of English Language Teaching, 2021)
Writing anxiety is a problem faced by the students in writing class. This anxiety can prevent the students from achieving the best understanding in writing. When a student is experiencing a writing anxiety, they will not be able to combine the sentences each other. This will make them get a low result in writing test. This research aims to see the correlation between writing anxiety and writing achievement of Paragraph Writing class in English Department at UniversitasNegeri Padang. This study used a descriptive research method. The population of this research was all English college students of the second semester World Health Organization were already learned Paragraph Writing course in January- June 2020. They were selected because they had taken a course on paragraph writing. The sample was 48 students taken using a cluster random sampling. The informasi were collected using questionnaire from Second Language Writing Anxiety Inventory(SLWAI) and writing test to get the result from the writing achievement, which has been administered twice in order to get more reprehensive information. The results show that SLWAI and writing test have nomor correlation with the Pearson Correlation( r=-. 052) which indicated that whenever students have a high writing anxiety so it is possible for them to get the high or low achievement itself. Furthermore, this research related to writing achievement and writing anxiety is suggested to do.